Predictive Value of Plasma Thrombomodulin in Preeclampsia and Gestational Hypertension - Boffa, Marie-Claire; Valsecchi, Luca; Fausto, Alfonso; Gozin, Danielle; Vigano’ D’Angelo, Silvana; Safa, Omid; Castiglioni, Maria Teresa; Amiral, Jean; D’Angelo, Armando (Thrombosis and Haemostasis, 1998)
In a prospective longitudinal study, 130 primigravidae at risk for preeclampsia were examined and plasma sampling performed in 45 of them. Plasma thrombomodulin (pTM) was sequentially measured at weeks 12, 24 and 32 of gestation and after delivery in 20 primigravidae who developed either mild preeclampsia (n = 8) or gestational hyper-tension (n = 12) between weeks 32 and 39 of gestation and in 25 (age-matched) primigravidae who had uneventful pregnancies. pTM elevations were not observed until week 32 in uneventful pregnancies, but were present by week 24 (p = 0.002) in patients who later developed hypertensive complications. A net individual pTM increase ≥4.2 ng/ml between weeks 12 and 24 (more than 8 times that of normotensive primigravidae) and/or pTM level ≥47.5 ng/ml at week 32 predicted the development of hypertensive complications with 80% accuracy. Serial pTM determinations can be useful to select pregnancies who may benefit from early pharmacological intervention.